Evaluation of short day local and exotic onion genotypes (Bangladesh Journal of Agriculture, 2023)
Onion is one of the important spices of daily dishes in Bangladesh and are shortage in production of the crop. Due to high photosensitivity in onion, only short-day types are suitable for cultivation in the particular agroclimatic condition of the country. But lack of high yielding potentiality in the existing cultivar along with limited variability within the available germplasm is the major drawback in onion production. To mitigate the problem, the present investigation was done to identify suitable short-day onion genotypes at the Regional Spices Research Centre, BARI, Gazipur during rabi 2018-19 and 2019-20. Twenty-nine local and exotic short-day onions were evaluated including two local checks BARI Piaz-1 and BARI Piaz-4. δ2p and PCV was higher than δ2g and GCV in almost all the traits studied and higher heritability (h2b) was observed for total bulb yield. Significant variations were found in morphological and physiological traits for bulb production. Considerably higher bulb length and diameter were found from Ac_G_18_379, Ac_B_18_413, Ac_B_18_420, Ac_B_18_428, BARI Piaz-4, Ac_B_18_419 and Ac_B_18_417. Minimum bulb splitting (%) and bolting (%) were obtained from the genotypes Ac_G_18_379, Ac_G_18_381, Ac_B_18_413 and BARI Piaz-4. Higher dry matter content was noted for the genotypes BARI Piaz-4 (17.9 %), Ac_B_18_425 (21.73 %) and Ac_G_18_384 (21.57 %) along with the TSS ranged from 10.5 to 17.780Brix. The maximum bulb yield was obtained from the genotype Ac_B_18_413 (20.69 t/ha), followed by Ac_G_18_383 (20.6 t/ha), Ac_B_18_419 (18.48 t/ha) and Ac_B_18_417 (18.2 t/ha). These genotypes could be recommended for commercial cultivation as well as to use in future onion breeding program.Bangladesh J. Agri. 2022, 47(2): 27-43